Cytotoxicity Assay From Fractions of Hedyotis corymbosa Extract Against Breast Cancer Cell Line T47D - Andriyani, Rina; Risdian, Chandra; Udin, Zalinar (Indonesian Research Gateway, 2011)
Drug discovery for cancer medication is the most important effort that researcher do ÃÂ at ÃÂ this time. Indonesia bio diversitiesÃÂ have ÃÂ possibility ÃÂ as ÃÂ a cancer medicine ÃÂ sources. Finding a herbal medicine for cancer treatment is a first step to find a right cancer medicine in the future.This research has already completed for the earlier another research.Some fractions of Hedyotis corymbosa extract has been analyzed using Sulforhodamine B method with ÃÂ UV wavelength ÃÂ 515 nm against T47D cell line, a human breast cancer. There are Hexane extract, Methylene chloride extract and Ethyl acetate extract,and give inhibitory concentration 50 (IC50) of 33.45 1g/ml, 54.59 1g/ml and 52.58 1g/ml, respectively. Ethanolic extract, ÃÂ itself ÃÂ has ÃÂ IC50 of 61.57 1g/ml, whereas IC50 value of ÃÂ Cisplatinum is 9.63 1g/ml. There is a difference between the ethanolic extracts with the other fraction.